CONTINUITY OF THE MANAS GROUP OF SITES AND KAYAKENT-KHOROCHOY CULTURE OF THE BRONZE AGE IN THE NORTHEAST CAUCASUS - Ataev, Gamzat Dibirovic; Ahundov, Tufan Isaak-oglu (History, Archeology and Ethnography of the Caucasus, 2022)
The article deals with the study of continuity of archeological formations in the Northeast Caucasus: the Manas group of sites of the early Middle Bronze and the early stage of the Late Bronze Age. As a result of the analysis of the archeological material, which includes settlements, burial structures and rituals, pottery, jewelry, tools, military equipment, we examined the issues of the decline of the Manas group sites and the emergence of a new archeological formation on its basis – the Kayakent-Khorochoy culture. The examined material demonstrates a smooth, evolutionary transition of the Manas group of sites into the Kayakent-Khorochoy culture. In its key cultural features (settlements and dwellings, pottery, weapons, jewelry and other equipment, except for burial structures and rites, antimonic pendants), the Kayakent-Khorochoy culture is genetically related to the previous Manas group of sites. The study of sites of the Middle and Late Bronze of Central Dagestan allows for deeper understanding of the issue of transformation of the Manas group of sites of the Early Middle Bronze into the Kayakent-Khorochoy culture. These studies are relevant for the determination of the issues of cultural genesis of the said region, the development of cultures of the Middle and Late Bronze Ages in the Northeast Caucasus, the identification of patterns of their development in the period under study.
Keywords: Northeast Caucasus; Dagestan; steppe; Middle Bronze; Manas group of sites; Kayakent-Khorochoy culture; burial grounds; burial mounds; tomb; stone box